2007
DOI: 10.1080/02713680601186698
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylprednisolone Pulse Treatment on Cytokine Network in Graves Ophthalmopathy

Abstract: The etiology of Graves ophthalmopathy (GO), representing the most common extrathyroidal manifestation of Graves disease, is multifactorial. Among multiple genetic, environmental, and endogenous factors, cytokines play a critical role in its etiopathogenesis. We studied an effect of glucocorticoid therapy on the serum IL-6, IL-4, and IL-13 levels in 18 GO patients. All the patients presented euthyroid GO with over 4 points according to the CAS classification (range 4-6; mean 4.94). The patients were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
4
10
0
1
Order By: Relevance
“…However, the mechanism by which DEX reduces the relapse rate of GD is not fully understood. DEX is a kind of glucocorticoid usually used in the treatment of Graves' ophthalmopathy (GO) and is one of the most effective medicines (14,15). Some reports showed that Treg cell count increased with DEX treatment in chronic idiopathic thrombocytopenic purpura and other autoimmune diseases (16,17).…”
Section: Cd25mentioning
confidence: 99%
“…However, the mechanism by which DEX reduces the relapse rate of GD is not fully understood. DEX is a kind of glucocorticoid usually used in the treatment of Graves' ophthalmopathy (GO) and is one of the most effective medicines (14,15). Some reports showed that Treg cell count increased with DEX treatment in chronic idiopathic thrombocytopenic purpura and other autoimmune diseases (16,17).…”
Section: Cd25mentioning
confidence: 99%
“…The most significant finding was a uniform decrease in IL-6 levels after 2 weeks and a sustained decrease after 6 months in 8/18 patients who had responded clinically to the steroids (mean CAS of 1.25). The levels of IL-4 and IL-13 did not have significant trends with treatment [13]. Although Th1- and Th2-like cytokines are involved in the pathogenesis of GD, efforts to correlate the balance in IL-12/IL-5 cytokines in GD patients did not strongly correlate with TED disease activity [4].…”
Section: Pathogenesismentioning
confidence: 99%
“…Thus, a high dose of steroid alone or in combination with radiotherapy has been employed successfully to reduce orbital inflammation and the severity of the ophthalmopathy [15,18]. However, longterm steroid administration is associated with significant side effects mainly Cushing's syndrome [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, longterm steroid administration is associated with significant side effects mainly Cushing's syndrome [18]. Low dose radiotherapy has been demonstrated to be effective in reducing the severity of Graves' ophthalmopathy with lasting results and minimal morbidity [10,15,20,27,33]. The effectiveness of radiotherapy may be limited in severe proptosis with a higher percentage of patients developing disease progression or no improvement following radiotherapy [10,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation